The influence of sowing dates on the yield capacity of soybeans sorts - Цехмейструк, М. Г.; Шеляків, В. О.; Шевніков, М. Я.; Литвиненко, О. С. (Scientific Progress & Innovations, 2018)
The results of the experiments confirm the possibility of obtaining stable yields by years due to the selection of the sowing date and the background of mineral nutrition. On average, in 2002–2005, the sort Romance marked a clear tendency to increase yields from early to late, regardless of backgrounds (from 1.73 t/ha to 2.08 t/ha on average for 4 years). In the sorts Mriia and Amethyst on the background of non-fertilizers, the same tendency appears, whereas in the background of the application of fertilizers the most optimal terms were earlier (the third decade of April and the first decade of May) than the late ones. The highest level of soybean productivity in 2006–2010 was obtained at the early (22.04) sowing date – 1.82 t/ha, and the worst indicators were obtained in late (21.05) sowing where the yield was 1.67 t/ha. In terms of sorts – the best results, for most of the time, except for late was obtained during the cultivation of the sort Romance, which provided 1.84–1.87 t/hectare of seeds. In late times, the third (06.05), the fourth (14.05) and the fifth (21.05) higher yields were obtained for the cultivation of the sort Annushka – 1.72–1.85 t/ha.